Directing Traffic: Regulation of COPI Transport by Post-translational Modifications - Luo, Peter M.; Boyce, Michael (Frontiers in Cell and Developmental Biology, 2019)
The coat protein complex I (COPI) is an essential, highly conserved pathway that traffics proteins and lipids between the endoplasmic reticulum and the Golgi. Many aspects of the COPI machinery are well understood at the structural, biochemical and genetic levels. However, we know much less about how cells dynamically modulate COPI trafficking in response to changing signals, metabolic state, stress or other stimuli. Recently, post-translational modifications have emerged as one common theme in the regulation of the COPI pathway. Here, we review a range of modifications and mechanisms that govern COPI activity in interphase cells and suggest potential future directions to address as-yet unanswered questions.